Pemanfaatan Artificial Intelligence dalam Penyusunan Instrumen Evaluasi Pembelajaran: Studi Kasus di SD Negeri 2 Merauke - Amri, Haerul; Fredy, Fredy; Yohanes, Rizki Adri; Rapsanjani, Hafsemi; Ismail, My (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The utilization of Artificial Intelligence (AI) in primary education presents a significant opportunity to improve the quality of learning assessment. However, in border regions such as SD Negeri 2 Merauke, the implementation of such technology faces considerable challenges. This study aims to explore educators' perceptions of using AI in the development of assessment instruments and to identify the obstacles and opportunities for its application. The research subjects included six classroom teachers, one principal, and two administrative staff members selected through purposive sampling based on their active roles in the assessment process. A qualitative approach was employed, using data collection techniques such as in-depth interviews, participant observation, and documentation. Data were analyzed using Miles and Huberman’s interactive model, and validity was ensured through source and technique triangulation. The findings reveal that most educators lack a clear understanding of AI concepts and practices but demonstrate a willingness to adopt innovations if supported by context-specific training. Key barriers include limited infrastructure, low digital literacy, and inadequate technical support. These findings highlight the urgency of building teacher capacity through localized training programs and formulating inclusive digital transformation policies for schools in border areas.